Embutido tipo salsicha utilizando carne mecanicamente separada de tilápia: uma alternativa para o aproveitamento de resíduo da filetagem - Lago, Amanda Maria Teixeira (2015)
The fish industry presents a large growth potential because their disposal can be processed into products with marketing uses. An alternative technology for better utilization of the edible part of the fish is the mechanically separated meat (MSM), which can be used as raw material in a range of products. However, there are few studies on its use in the preparation of sausages. Given this situation, the aim of this study was to develop and characterize sausages made with increasing inclusion of MSM. In addition to analyze which formulation was the most accepted, the study aimed to set its shelf life, based on laboratory tests. In the first step, different formulations of sausages were developed with 0, 25, 50, 75 and 100% of MSM. The nutritional value, physical and chemical properties, microbiological aspects and sensory quality of each formulation were evaluated. The last phase of the study consisted of the analysis of the shelf life of the best formulation for a period of 60 days of storage under freezing at -10°C. In terms of technological and nutritional parameters, the use of MSM from tilapia in the production of sausages did not depreciate the quality of the final product. It was found that, in general, all developed sausages met the requirements established by current legislation, referring to the cooked meat sausages. The results shown that all sausage samples met the established microbiological standards, indicating that the entire process was conducted in hygienic conditions. Regarding the sensory evaluation, it was found that consumers indicated higher acceptance rate for the formulation presenting balanced addition of MSM and tilapia fillet (50%). Thus, for having stood out among the others, with respect to all parameters analyzed, the formulation made with 50% of CMS was selected for shelf life determination. It was found that the storage time had a significant influence on physic and chemical parameters of the final product. However, the nutritional and microbiological quality of tilapia sausage was maintained within the required by current Brazilian legislation. The acceptance of the product was not compromised since the sensory quality of the sausage were maintained, according to the consumers. Given the results presented, we can guarantee the shelf life of the sausage containing 50% of MSM and Nile tilapia (Oreochromis niloticus) in 60 days. The development of this product is a viable alternative to the use of residues of this species of fish.